LABOR SATISFACTION AND ORGANIZATIONAL COMMITMENT: A CORRELATIONAL STUDY IN MEXICO - Mapén Franco, Fabiola de Jesús (Revista Inclusiones, 2020)
Job satisfaction and organizational commitment are theoretical constructs whose importance is evident when analyzing their effects from the thresholds of Organizational Psychology, from which they are recognized as predictors of performance and productivity, which are fundamental for the management of organizations. Therefore, the purpose of the present study was to measure the degree of job satisfaction and organizational commitment of teachers in basic education who promoted pedagogical technical advisors when presenting a promotion evaluation, driven by the Educational Reform implemented in Mexico from 2013 to 2019. The design of the research is descriptive-correlational with a quantitative approach, the reliability of the research instruments was determined from the Cronbach Alpha coefficients: 0.93 for job satisfaction and 0.90 for organizational commitment. Among the results obtained, the statistically significant positive relationship between job satisfaction and organizational commitment was confirmed globally; however, in the analysis of dimensions of the constructs: the affective commitment, continuity, satisfaction with the benefits received and with the supervision presented the lowest average scores.